Solution of a Fuzzy Assignment Problem by using Branch-and-Bound Technique with application of linguistic variable - Gotmare, Anil (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
In this paper Branch and bound technique is applied to assignment problem with fuzzy cost with objective to minimise cost, fuzzy cost is assumed as triangular fuzzy number, Yager’s ranking method has been used for ranking the fuzzy numbers, after transforming assignment problem into a crisp one using linguistic variables, assignment problem is solved by branch and bound technique. To deal with fuzzy assignment problem with qualitative data, linguistic variable helps to convert qualitative data into quantitative data.